An Archaeological landscape of Sharif Abad (Solgi) settlement area in the Gamasi-Ab River Basin in Central Zagros - NOURALLAHI, Ali (Historia i Świat, 2022)
Solgi or Sharif Abad tepe (A&B) is one of the larger settlement sites of the Gamasi-Ab river basin in Nahavand plain. This site lies at the intersection of old ancient roads that go from Sahne, Harsin and Kangavar to Nihavand and the other eastern regions. In the study of this area, pottery from the Early Bronze Age (Godin IV-Yanik, Kura-Araxes), pottery related to Godin III, II and pottery of the historical period were obtained. The examination of these pottery artefacts reveals extensive cultural exchanges of the inhabitants of the region with the northwestern and neighboring areas in the Bronze and Iron Ages. In addition, a closer examination of the lifestyle in this settlement area gives us a complete view of these people’s use of biological resources and their interaction with the environment. Among the reasons for the location and development of this settlement in the Bronze and Iron Age the main one was easy access to water resources and fertile agricultural lands. This article provides a brief overview of the geographical situation of the region and the history of archaeological research conducted in Nihavand and then focuses on the natural landscape of Sharif Abad. The next part of it describes the archaeological data from this location and analyzes its chronology. The article is concluded by a succinct summary.